Descarte do lixo e seu impacto no ambiente e saúde: percepção das comunidades indígenas de Mangueirinha – PR - Marcondes, Camila (2014)
The historical loss of earth and natural resources and the constant inter-ethnic contacts had changed at least some part of the Indian economies dependents on the capitalist market logic and transformed the consumption pattern of the villages. There‟s some dependence related to their consumed food, in general bought, that raises the number of packaging and tailings to dispose. However, the garbage collect on the villages is still precarious, that originates problems on this discard. In visit to the Indian earth Mangueirinha, it was observed the presence of trash around the houses with industrialized products packaging, like plastic bottles, cans of soda, packets of chips and some disposable diapers. In this contest, the research had as central objective analyze the perception of the local people about the garbage discarding and It‟s impact on village‟s healthy and environment. The specific objectives of the research were: to do the cultural food and social-economic profiles and to identify the Indian methods of garbage discarding utilized by the investigated community and to identiy perception about environment and It‟s impact on healthy. For the investigation of that case we carried out a qualitative study with thirteen indigenous. A pre-prepared script was used to guide the questions regarding the respondent profile, what methods are used to dispose of trash and how they perceive the relationship between environment and health. The interviews were conductedat Kokoj Ty Han Já School and home visits. The research results show that the Indians perform cultural activities aiming to keep alive the customs and traditional aspects of the village, but in daily life, several segments are affected by non-indigenous influence, such as education, health and eating habits. With regard to the perception of environmental problems in the indigenous area or around it, formed three different groups of residents that identify the main environmental problem as deforestation, the second group that identifies as pollution and the third group that believes that no environmental problem exists on indigenous lands. Interethnic contacts changed the perception of what they consider items necessary for their well-being. In seeking to gain access to consumer goods they diversify their livelihoods, combining wage labor to other sources of income. What is involved in the release of non-organic waste on the environment and been a source of health problems. Residents listed solutions to the problems faced, such as increasing the frequency of collection and the points in passing garbage truck, build warehouses for the correct storage and conducting community guidelines for the reuse of organic waste, waste separation and correct disposal. Therefore, they realize the importance of preserving the environment for their quality of life, but in everyday life they lack structure and availability of public services of garbage collection and educational activities concerning the management of solid waste.